IL-7R signaling in regulatory T cells maintains peripheral and allograft tolerance in mice - Schmaler, Mathias (Proc Natl Acad Sci U S A, 2015)
Foxp3(+)CD4(+) regulatory T cells (T(reg)) have a crucial role in controlling CD4(+) T-cell activation, proliferation, and effector function. However, the molecular mechanisms regulating T(reg) function remain poorly understood. Here we assessed the role of IL-7, a key cytokine regulating T-cell homeostasis, in suppressor capacity of T(reg). Using a skin allograft model in which transplant acceptance is controlled by the number of transferred T(reg), we find that T(reg) impair the proliferation of allogeneic CD4(+) T cells, decrease production of IFNγ by effector T cells, and prevent early and increase late IL-7 induction by lymph node stromal cells. Increased IL-7 availability enhanced T(reg) survival, stabilized T(reg) molecular signature, enhanced surface IL-2Rα expression, and improved IL-2 binding of T(reg), which diminished proliferation of alloreactive CD4(+) T cells. Sequestration of IL-7 or impairment of IL-7R signaling after allograft transplantation abolished T(reg)-mediated tolerance by limiting their suppressive capacity. Aged Il7rα-ΔT(reg) mice displayed mild symptoms of autoimmunity correlating with impaired expansion of effector T(reg) in response to IL-2. Thus, IL-7R signaling on T(reg) supports the functional activity of effector T(reg) by increasing their IL-2 sensitivity in the lymph node during peripheral and allograft tolerance.